2016
DOI: 10.1515/hukin-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Differences between Barbell and Body Optimum Power Loads in the Jump Squat Exercise

Abstract: This study compared the values of bar-peak force (PFBar) and power (PPBar), body-peak force (PFBody) and power (PPBody) and bar-mean propulsive power (MPPBar) in different jump-squat (JS) conditions: unloaded condition (UC); bar-loaded condition (BLC) and optimum bar-MPP condition (OBC). Twenty-five soccer players performed the JS using a bar with negligible mass (UC), using the Smith-machine bar (BLC) and using the load capable of maximizing the bar-MPP (OBC). The PFBody was significantly higher in the UC (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…These data are very similar to those described herein, confirming the usefulness of the bar-power approach in assessing athletic performance, especially in elite athletes. The opportunity to use ranges of loads which optimize the force and velocity applied to the barbell at the same time 15,26 (instead of only considering the maximum mass moved during a maximum effort [i.e., 1RM]) may better reflect the abilities required in sport-tasks, where athletes are frequently required to move substantial amounts of loads at high speeds (e.g., the BM during a vertical jump or maximal sprints). 25,27,28 Although this mechanical parameter does not represent "total power of the system" (i.e., system-power) 15,16 , the bar-power output can be used not only to monitor strength and power capacities, but also to discriminate athletes with different performance levels and training backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are very similar to those described herein, confirming the usefulness of the bar-power approach in assessing athletic performance, especially in elite athletes. The opportunity to use ranges of loads which optimize the force and velocity applied to the barbell at the same time 15,26 (instead of only considering the maximum mass moved during a maximum effort [i.e., 1RM]) may better reflect the abilities required in sport-tasks, where athletes are frequently required to move substantial amounts of loads at high speeds (e.g., the BM during a vertical jump or maximal sprints). 25,27,28 Although this mechanical parameter does not represent "total power of the system" (i.e., system-power) 15,16 , the bar-power output can be used not only to monitor strength and power capacities, but also to discriminate athletes with different performance levels and training backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, there is a significant limitation in considering a given scalar variable (i.e., mass) as a "strength measurement". 15,26 In this context, it is critical to emphasize that the ability to efficiently accelerate relative loads (and thus reach higher movement velocities) is a selective factor in different sport disciplines. 12,25,30,31 The finding that the bar-power output is more strongly associated with sport-performance than 1RM measures indicates that this novel and alternative method might be an effective way to assess elite athletes.…”
Section: Discussionmentioning
confidence: 99%
“…force plates and linear transducers) that are often unavailable in the field setting. Notwithstanding, it was reported that the maximal power output usually ranges from 0% to 30% of the squat 1-RM (14,18,30), and also shown in a direct optimum load vs body mass comparison (29). Jump-squat training is characterized by repetitive explosive concentric take-offs followed by repetitive eccentric landings.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Thus, muscle power stands out as the primary physical capacity in motor gestures during a rugby game 2 . Although many studies focus on strategies for increasing lower limb muscle power 3 , we highlight the need to specifically optimize muscle power of upper limbs (PUL) in rugby. Rugby players on average perform 106 passes per game 4 , up to 50% of which are long distance 5 with the objective of, at a given moment, create numerical advantage in the attack 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The development and maintenance of muscular strength is fundamental during the sports season 6 . Thus, its periodic evaluation is necessary for the prescription of optimal loads for training muscle power 3,6,7 . The training planning for high-performance athletes should consider that the development of muscle power lies on the application of force at high speeds and that, for most sports, what really matters is not the maximum strength, but rather the rate of force development applied within the sporting gesture.…”
Section: Introductionmentioning
confidence: 99%